ROLE OF DIGITAL TRANSFORMATION IN SCIENCE TEACHING - Gulnora Narmatovna Halmatova; Nematulla Abdukarimovich Gulbayev (Western European Studies, 2024)
The article is devoted to the place of digital transformation in the teaching of subjects, and the problems of teaching Russian language and literature using digital technology are presented
Keywords: digital technology; mobile device; Russian language